1987
DOI: 10.1007/bf02577993
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional echocardiography in the diagnosis of intracardiac masses: A prospective study with anatomic validation

Abstract: The accuracy of two-dimensional echocardiography in the detection of intracardiac masses was verified in 334 patients who underwent cardiac catheterization in our laboratory over 21 consecutive months. A complete two-dimensional echocardiographic (2DE) examination was performed a day before catheterization. The presence or absence of a mass was verified at surgery in 77 patients who successively underwent mitral or aortic valve replacement (51), left ventricular aneurysmectomy with or without myocardial revasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
1
5
1
Order By: Relevance
“…27,28 Sheiban et al reported that two-dimensional echocardiography has an 82.2% sensitivity and 95.3% specificity in detection of intracardiac masses. 29 Our study shows more common atrial thrombus among female and diabetic patients compared to male and nondiabetic patients, but there were not any statistical significance probably due to limited number of the patients. Stavroulopoulos et al also reported higher frequency of atrial thrombus in female patients.…”
Section: Discussioncontrasting
confidence: 73%
“…27,28 Sheiban et al reported that two-dimensional echocardiography has an 82.2% sensitivity and 95.3% specificity in detection of intracardiac masses. 29 Our study shows more common atrial thrombus among female and diabetic patients compared to male and nondiabetic patients, but there were not any statistical significance probably due to limited number of the patients. Stavroulopoulos et al also reported higher frequency of atrial thrombus in female patients.…”
Section: Discussioncontrasting
confidence: 73%
“…The compression technique we used has greater than 90% sensitivity for proximal DVT and approximately 50% sensitivity for distal DVT (Jang et al, 2004;Goodacre et al, 2005). After finding no evidence of DVT, we performed an echochardiogram to assess for intracardiac thrombus or mass and more definitively rule out atrial fibrillation, other likely sources of thromboembolism that can be identified using two-dimensional ultrasound (Abbott et al, 1982;Sheiban et al, 1987). We did not pursue the possible presence of a patent foramen ovale by injection of air contrast since we had not identified a DVT and had little experience with the technique.…”
Section: Discussionmentioning
confidence: 99%
“…18 TTE examinations, using apical four-chamber and subcostal views, can be used as a screening tool with sensitivity and specificity of 82.2% and 95.3%, respectively. 19 Furthermore, magnetic resonance imaging and CT scans have been used to detect intracardiac thrombi. On the one hand, catheter removal may prevent CRAT relapses, thromboembolism, and septic complications.…”
Section: Discussionmentioning
confidence: 99%